Antihypertensive Medication Adherence and Medical Costs, Health Care Use, and Labor Productivity Among People With Hypertension - Jun Soo Lee; Raul Segura Escano; Nicole L. Therrien; Ashutosh Kumar; Ami Bhatt; Lisa M. Pollack; Sandra L. Jackson; Feijun Luo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Hypertension affects nearly half of US adults yet remains inadequately controlled in over three‐quarters of these cases. This study aimed to assess the association between adherence to antihypertensive medications and total medical costs, health care use, and productivity‐related outcomes. Methods and Results We conducted cross‐sectional analyses using MarketScan databases, which included individuals aged 18 to 64 years with noncapitated health insurance plans in 2019. Adherence was defined as ≥80% medication possession ratio for prescribed antihypertensive medications. We used a generalized linear model to estimate total medical costs, a negative binomial model to estimate health care use (emergency department visits and inpatient admissions), an exponential hurdle model to estimate productivity‐related outcomes (number of sick absences, short‐term disability, long‐term disability), and a 2‐part model to estimate productivity‐related costs in 2019 US dollars. All models were adjusted for age, sex, urbanicity, census region, and comorbidities. We reported average marginal effects for outcomes related to antihypertensive medication adherence. Among 379 503 individuals with hypertension in 2019, 54.4% adhered to antihypertensives. Per person, antihypertensive medication adherence was associated with $1441 lower total medical costs, $11 lower sick absence costs, $291 lower short‐term disability costs, and $69 lower long‐term disability costs. Per 1000 individuals, medication adherence was associated with lower health care use, including 200 fewer emergency department visits and 90 fewer inpatient admissions, and productivity‐related outcomes, including 20 fewer sick absence days and 442 fewer short‐term disability days. Conclusions Adherence to antihypertensives was consistently associated with lower total medical costs, reduced health care use, and improved productivity‐related outcomes.